KETERAMPILAN GURU MENGGUNAKAN MEDIA DALAM PEMBELAJARAN SEJARAH DI SMP N II PADANG - Harianto, Mendi; Kaksim, Kaksim; Nurhuda, Ahmad (Pendidikan Sejarah, 2014)
The research is motivated by the teacher is often incorrectly choose the media that fits the material being taught, or ise the same media to any teaching and learning process. This study aims to abtain data, information about (1) Skills teachers choose various types of media and understand the function of each mediun in the learning, (2) Skill teachers to design a learning media appropriate to the learning objectives, learning materials, teaching method and digestibility ability learners in learning history, (3) a history teacher organizing skills of learners in the use of media in teaching history. Thiss research study evaluating the qualitative analysis. The experiment was conducted at SMP II Padang. Research informants were teachers who teach subjects taught in history class VII numbered 2, then the principal and vice curriculum. Based on the result: 1) Skill teachers in selecting and using instructional media in the teaching of history in accordance with the function of learning media including a pretty, 2) Skill teachers in designing instructional media appropriate to the learning objectivesÂ are adequate and skill of teachers in engaging student to use instructional media including less.